2020
DOI: 10.1002/dneu.22778
|View full text |Cite
|
Sign up to set email alerts
|

Type II interferon signaling in the brain during a viral infection with age‐dependent pathogenesis

Abstract: Viral infections of the central nervous system (CNS) often cause disease in an agedependent manner, with greater neuropathology during the fetal and neonatal periods. Transgenic CD46+ mice model these age-dependent outcomes through a measles virus infection of CNS neurons. Adult CD46+ mice control viral spread and survive the infection in an interferon gamma (IFNγ)-dependent manner, whereas neonatal CD46+ mice succumb despite similar IFNγ expression in the brain. Thus, we hypothesized that IFNγ signaling in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The results showed that markedly enriched terms included ion transport, type II interferon signaling, and synaptic signaling. Interestingly, type II interferon signaling and ion transport have been reported to be associated with central nervous system inflammation in previous studies 23 , 24 .…”
Section: Discussionmentioning
confidence: 88%
“…The results showed that markedly enriched terms included ion transport, type II interferon signaling, and synaptic signaling. Interestingly, type II interferon signaling and ion transport have been reported to be associated with central nervous system inflammation in previous studies 23 , 24 .…”
Section: Discussionmentioning
confidence: 88%
“…Endocytosis is used by SARS-CoV-2 to enter the host cell and induce COVID-19 [89] and the alteration in the endocytic pathway is thought to play a key role in the pathogenesis of NDs [90]. Type II interferons (IFNs) have been linked to higher COVID-19 severity [91] and the development of ND [92]. It is proposed that astrocyte SREBPs are involved in neuronal function in the central nervous system [93].…”
Section: Discussionmentioning
confidence: 99%